Socio-cultural barriers to child sexual abuse investigation in Uganda: Experiences of police officers at Kamuli District central police station - Waiswa Emmanuel Kaako; Kiconco Milliam; Namara Susan; Namubiru Lydia (International Review of Social Sciences Research)
Child sexual abuse has been widely recognised as a global crisis and a violation of fundamental rights of children. Irrespective of this recognition, child sexual abuse remains pervasive, underreported and poorly investigated. This paper forms part of a qualitative case study that aimed at establishing challenges faced by police officers in investigating cases of child sexual abuse in Kamuli District, Eastern Uganda. The study utilised purposive sampling to select 14 police officers from three departments of Kamuli District central police station which included; Criminal Investigation Department, Child and Family Protection Unit and Sexual Gender-Based Violence Department. Data collection was conducted using face-to-face in-depth interviews. The instruments of data collection were the semi-structured interview guides while data analysis was done using thematic analysis. One of the major themes that were generated through interviews with police officers included the socio-cultural factors that hinder them from investigating child sexual abuse. Discussed in this paper are these factors, which include; failure and delayed disclosure of abuse/abusers, ignorance, community beliefs, inadequate cooperation from parents and guardians, and taboos regarding discussion of sex in public. Apart from reflecting limited education and awareness about the impact of child sexual abuse, these challenges show that in Uganda, child sexual abuse is taken as a private matter which should be settled informally between the perpetrators and victims’ families. The findings of this study make a contribution to limited research about child sexual abuse in Uganda and to the policy-making and practice on crimes of the kind.